Comparison of Lymphocyte Subset Populations in Children From South Africa, US and Europe - Helen Payne; Denise Lawrie; Martin Nieuwoudt; Mark Fredric Cotton; Diana M. Gibb; Abdel Babiker; Debbie Glencross; Nigel Klein (Frontiers Media S.A., 2020)
Background: Typically, African healthcare providers use immunological reference intervals adopted from Europe and the United States (US). This may be inappropriate in a setting with many differences including exposure to different environmental stimuli and pathogens. We compared immunological reference intervals for children from Europe and the US with South African children to explore whether healthy children living in settings with high rates of infectious diseases have different baseline immunological parameters.Methodology: Blood was taken from 381 HIV-uninfected children aged between 2 weeks and 13 years of age from a Child Wellness Clinic in an informal settlement in Cape Town to establish local hematological and lymphocyte reference intervals for South African children. Flow-cytometry quantified percentage and absolute counts of the B-cells, NK-cells, and T-cells including activated, naïve, and memory subsets. These parameters were compared to three separate studies of healthy children in Europe and the US.Results: Increased activated T-cells, and natural killer cells were seen in the younger age-groups. The main finding across all age-groups was that the ratio of naïve/memory CD4 and CD8 T-cells reached a 1:1 ratio around the first decade of life in healthy South African children, far earlier than in resource-rich countries, where it occurs around the fourth decade of life.Conclusions: This is the largest data set to date describing healthy children from an African environment. These data have been used to create local reference intervals for South African children. The dramatic decline in the naïve/memory ratio of both CD4 and CD8 T-cells alongside increased activation markers may indicate that South African children are exposed to a wider range of environmental pathogens in early life than in resource-rich countries. These marked differences illustrate that reference intervals should be relevant to the population they serve. The implications for the developing pediatric immune system requires further investigation.